Episodic Hyponatremia in Acute Intermittent Porphyria: A Case Report - Khatiwada, S; Baral, B; Lamichhane, S; Shrestha, B; Ranjan, MK (Journal of Diabetes and Endocrinology Association of Nepal, 2024)
Background: Acute intermittent porphyria (AIP) is an uncommon, ubiquitously distributed autosomal dominant disorder with low penetrance characterized by decreased enzyme activity of hydroxymethylbilane synthase (HMBS) an enzyme of heme synthesis pathway. It is often an elusive diagnosis due to rarity and non-specific signs and symptoms.Case report: A 28 years old female from Nawalparasi (district in central Nepal) presented with history of recurrent episodes of abdominal pain and vomiting. Her current episode began two weeks before presentation to our center. Abdominal pain was diffuse, colicky in nature without exacerbating or relieving factor. There was no postural or diurnal variation. On examination, there was no tenderness and abdominal examination findings were unremarkable. Her biochemical investigations were unremarkable except for severe hyponatremia (S. Na of 100mmol/L) which was SIADH/SIADH like presentation (Table 1 and Table 2). Severe episodic hyponatremia, port-wine color of urine, gastrointestinal symptoms and previous hospital stay two years back with similar episode of hyponatremia and abdominal pain were valuable clues for suspicion of acute porphyria. On further evaluation, patient was found to have presence of porphyrogenic precursors in urine and diagnosis of acute intermittent porphyria was confirmed. After diagnosis, she was managed conservatively with carbohydrate loading with intravenous dextrose, opioids and pregabalin as analgesics. Her symptoms gradually improved, hyponatremia subsided and was discharged in normal condition.Conclusion: Acute intermittent porphyria has signs and symptoms common to several clinical, neurological, psychiatric and gastroenterological pathologies, which complicate diagnosis. In young patients with hyponatremia (with SIADH –like picture), AIP should be considered in differential diagnosis.